2001
DOI: 10.1086/323269
|View full text |Cite
|
Sign up to set email alerts
|

[ITAL]Chandra[/ITAL] Observation of the Radio Source/X-Ray Gas Interaction in the Cooling Flow Cluster Abell 2052

Abstract: We present a Chandra observation of Abell 2052, a cooling flow cluster with a central cD that hosts the complex radio source 3C 317. The data reveal "holes" in the X-ray emission that are coincident with the radio lobes. The holes are surrounded by bright "shells" of X-ray emission. The data are consistent with the radio source displacing and compressing, and at the same time being confined by, the X-ray gas. The compression of the X-ray shells appears to have been relatively gentle and, at most, slightly tran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
275
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 263 publications
(297 citation statements)
references
References 16 publications
21
275
1
Order By: Relevance
“…In the densest central region with high cooling rate, the hot gas atmosphere continues to loose energy in the form of radiation (mostly in X-rays). The inferred short radiative cooling time towards (or at) the centre (shorter than the age of the cluster) indicates that the gas located at the centre cools faster than the gas in the outer part of the cluster and hence gas flows towards the core to maintain hydrostatic equilibrium (Fabian 1994;Blanton et al 2001a). The excess gas in the central region of the cluster subsonically flows towards the core and leads to the for-studies of cool core clusters using Chandra and XMM-Newton observatories revealed that the interaction of radio jets originating from the core of the cluster with the ICM results in formation of cavities, shocks, ripples etc.…”
Section: Introductionmentioning
confidence: 99%
“…In the densest central region with high cooling rate, the hot gas atmosphere continues to loose energy in the form of radiation (mostly in X-rays). The inferred short radiative cooling time towards (or at) the centre (shorter than the age of the cluster) indicates that the gas located at the centre cools faster than the gas in the outer part of the cluster and hence gas flows towards the core to maintain hydrostatic equilibrium (Fabian 1994;Blanton et al 2001a). The excess gas in the central region of the cluster subsonically flows towards the core and leads to the for-studies of cool core clusters using Chandra and XMM-Newton observatories revealed that the interaction of radio jets originating from the core of the cluster with the ICM results in formation of cavities, shocks, ripples etc.…”
Section: Introductionmentioning
confidence: 99%
“…By examining the density profiles of two clusters, Abell 2052 ( fig. 2 of Blanton et al 2001), and Hydra A ( fig. 3 of David et al 2001), I find that condition (9) for instability at the outermost segment of the shell is fulfilled under the following conditions.…”
Section: Clustersmentioning
confidence: 96%
“…Finally, less gas cools to low temperatures at the centers of cool core clusters, groups, and individual ellipticals than expected unless something heats the gas, and AGNs are the leading candidates. In cool core clusters, X-ray deficits ("radio bubbles") have been found at the locations of the lobes of the radio sources associated with the brightest cluster galaxies (BCGs; Fabian et al 2006;Blanton et al 2001); similar radio bubbles are seen in groups and individual elliptical galaxies. "Ghost bubbles"' at larger radii are also seen which lack high frequency radio emission.…”
Section: Agn Feedback In Early-type Galaxiesmentioning
confidence: 99%